2016
DOI: 10.12968/hmed.2016.77.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Which mesh or graft? Prosthetic devices for abdominal wall reconstruction

Abstract: This article reviews the ever-increasing number of prosthetic devices--both synthetic mesh and biologic grafts--now in use for abdominal wall reconstruction. It also introduces a novel hybrid synthetic/biologic graft (Zenapro) and suture passer device (Novapass).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Reabsorbable and permanent surgical meshes are extensively used in abdominal surgery . Although most available materials are safe and biocompatible, there are common drawbacks associated to the use of inert surgical meshes including infection, fibrosis, inflammatory reaction, and foreign body reaction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reabsorbable and permanent surgical meshes are extensively used in abdominal surgery . Although most available materials are safe and biocompatible, there are common drawbacks associated to the use of inert surgical meshes including infection, fibrosis, inflammatory reaction, and foreign body reaction .…”
Section: Discussionmentioning
confidence: 99%
“…Tensionless repair of abdominal wall defects is one of the major clinical challenges in abdominal surgery, since reconstruction under tension is associated with surgical failure and high recurrence rate . In cases in which native tissue is damaged or absent, it is necessary to use prosthetic materials allowing an effective abdominal wall closure.…”
Section: Introductionmentioning
confidence: 99%
“…As it is well known that an ideal graft should have characteristics such as strong, inert, resistant to infection, low recurrence rate, high quality of life and good value. Ongoing advancements in techniques and technology will continue to help surgeons tailor the graft to the clinical scenario (30). Therefore, it can be concluded that the SGGEP meninges graft is more effective for managing abdominal wall defects than ADM.…”
Section: Discussionmentioning
confidence: 99%
“…Absorbable materials, also known as biosynthetic or bioabsorbable, like polyglactin 910 (Vicryl®), polyglycolic acid (Dexon TM ), polyglycolic acid: Trimethylene carbonate (Bio A®) or a copolymer of glycolide lactide and trimethylene carbonate (TIGR®) (Figure 4) [93] were introduced based on the idea that full reabsorption of the material into the patients´tissue would leave no foreign material behind. When the absorbable material is introduced as a barrier, separation is achieved between the implant and viscera until the mesh becomes covered by a neoperitoneum that prevents adhesion formation [94].…”
Section: Absorbable Materialsmentioning
confidence: 99%